2019
DOI: 10.1101/cshperspect.a033951
|View full text |Cite
|
Sign up to set email alerts
|

Functional Modules of the Proteostasis Network

Abstract: Cells invest in an extensive network of factors to maintain protein homeostasis (proteostasis) and prevent the accumulation of potentially toxic protein aggregates. This proteostasis network (PN) comprises the machineries for the biogenesis, folding, conformational maintenance, and degradation of proteins with molecular chaperones as central coordinators. Here, we review recent progress in understanding the modular architecture of the PN in mammalian cells and how it is modified during cell differentiation. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
166
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 179 publications
(169 citation statements)
references
References 174 publications
1
166
0
2
Order By: Relevance
“…We previously showed that the TIS granule network localizes to the surface of the rough ER, which is the primary site of protein synthesis in most cells (9). As large proteins are more difficult to fold and proteins with large IDRs have a tendency to aggregate (24,25), we propose that translation in TIS granules provides a favorable environment during translation and folding of 'difficult to express' proteins under physiological conditions. This is based on the recent finding that RNA has a very potent chaperone function in vitro.…”
Section: Discussionmentioning
confidence: 97%
“…We previously showed that the TIS granule network localizes to the surface of the rough ER, which is the primary site of protein synthesis in most cells (9). As large proteins are more difficult to fold and proteins with large IDRs have a tendency to aggregate (24,25), we propose that translation in TIS granules provides a favorable environment during translation and folding of 'difficult to express' proteins under physiological conditions. This is based on the recent finding that RNA has a very potent chaperone function in vitro.…”
Section: Discussionmentioning
confidence: 97%
“…The specific changes we observed herein focused our attention on the co-chaperone components (CARE) managing Hsp70 control of client folding as a central player in aging. In particular, the Bag3 response, being one of the largest differential responses detected, is involved in autophagic pathways, suggests that core chaperone associated degradation pathways associated with autophagy may be central to the management of AM and AT2 cells during aging, as suggested previously for other aging-related aggregation prone states (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28). These observations raise the possibility that aging of the lung, a major contributor to the decline of lung function in response to environmental stress over a lifetime (9), is, at least in part, an uncharacterized aggregation prone disease, perhaps in response to supersaturation (83,84) that must be precisely managed by the extensive Bag and DnaJ families through CARE over a lifespan.…”
Section: Discussionmentioning
confidence: 69%
“…Additionally, we observed changes in the expression of multiple proteostasis components involved in the functionality of the Hsp70 and Hsp90 core chaperome complexes, which have previously been linked to the management of neurodegenerative and other protein misfolding challenges during aging (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28). The specific changes we observed herein focused our attention on the co-chaperone components (CARE) managing Hsp70 control of client folding as a central player in aging.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations